Psi Chi at 90 Years: The International Honor Society in Psychology - Harold Takooshian (Peoples' Friendship University of Russia (RUDN University), 2019)
In 2019, Psi Chi celebrates its 90th and 10th birthdays as the National and International Honor Society in Psychology. This review of the glorious history of Psi Chi is in three parts: (1) its current mission, serving over 750000 life members in 1130 college campuses world-wide; (2) its humble but inspiring origins in 1929 at Yale University; (3) four points of impressive courage within the history of Psi Chi - in 1929, 1959, 1981, and 2009; and also includes a bibliography, for international and U.S. readers to access prior histories of Psi Chi.